(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To evaluate the effect of Nguyen Van Huong health-preversing exercise on isomnia in patients with cervicobrachial syndrome. Subjects: A total of 50 inpatients aged 38 to 80 years diagnosed with insomnia and cervicobrachial syndrome at Department of Traditional Medicine, Saint Paul General Hospital, from October 2024 to July 2025. Methods: A clinical interventional study with a pre- and post-treatment comparison. Patients were received treatment for cervicobrachial syndrome using electro-acupuncture and acupressure massage following the Ministry of Health’s protocol, combined with Nguyen Van Huong health-preserving exercise during a 15-day period. Results: After treatment, the average sleep duration increased from 3.54 ± 0.84 (hours) to 5.26 ± 0.85 (hours); sleep onset latency decreased from 80.80 ± 31.93 (minutes) to 42.60 ± 25.50 (minutes); PSQI score decreased from 17.22 ± 1.88 to 12.26 ± 2.13 (points); VAS decreased from 5.80 ± 0.40 to 3.30 ± 0.51 (points). All changes were statistically significant (p < 0.05). Conclusion: The Nguyen Van Huong health-preserving exercise method helps improve sleep duration, sleep onset latency, and reduce PSQI scores in patients with cervicobrachial syndrome.